Los manglares de México: una revisión - López Portillo, Jorge; Ezcurra, Exequiel (Instituto de Ecología, A.C., 2016)
The bibliographical information in México´s mangroves was reviewed, starting with biogeography. The diversity and composition of mangroves on the two coasts as well as their limits of distribution are described. The distribution, composition and physiognomy of mangrove communities are influenced by the latitudinal changes in the temperature and precipitation, but they depend locally on the geomorphology, the substrate, the salinity, the inundation and the relief. The studies reviewed suggest that the biotic interactions could also influence the observed zonation patterns and that he physiological and ecological optimum of the species do not always coincide spatially. The studies on litterfall have been carried out in the Gulf of México and Pacific Ocean coasts. The papers on leaf decomposition and its dynamic are also reviewed, along with those on phenology and the deforestation estimates which seems to be 5% per year. Finally, an analysis was made of the sources of mangrove forests perturbation. The main conclusion is that the challenges are very large and that more studies are required.